GAMBARAN FENOMENA FEAR OF MISSING OUT (FoMO) PADA GENERASI Z DI KALANGAN MAHASISWA - Cahyadi, Andi (Widya Warta, 2021)
This research was descriptive quantitative research. The purpose of this study was to describe the phenomenon of Fear of Missing Out in generation Z among college students. The subjects of this study were 277 college students which were selected through purposive random sampling, with criteria such as 19-23 years of age, male and female sex, college students who were still actively studying in Madiun, and active users of social media The FoMO scale used in data collection of this study was made by the researcher himself with reference to three aspects presented by Przyblylski, et al. Based on the trial results, the FoMO scale had high validity and reliability, namely with the internal consistency of .758, with the correlation coefficient of total statement items ranging from .343 to .599. The data obtained were analyzed using descriptive analysis. The result showed that there were 86.64% or a total of 240 subjects showing symptoms of FoMO in the sufficient category. Based on gender classification, it was found that out of 48 male students, 87.5% or a total of 42 subjects showed symptoms of FoMO in the sufficient category. While out of 229 female students, there were 86.46% or a total of 198 subjects showing symptoms of FoMO in the moderate category. Â